To Bend the Curve of Terrestrial Biodiversity, Place Agency Centre Stage - Garcia, C.; Savilaakso, S.; Sassen, M.; Stoudmann, N.; Verburg, R.W.; Quétier, F.; Araújo, M.B.; Bastin, J.; Boutinot, L.; Dessard, H.; Dray, A.; Fernbach, P.; et al. (MDPI, 2020)
Leclère et al.1 have outlined the possibility of a biodiversity transition for the 21st century, a line of thinking equivalent to the Forest Transition theory and what it says about forest cover globally2. The authors use a suite of global models to explore the impacts on global biodiversity of interventions on land-use, consumption and production patterns. They outline six strategies that have the potential to stop the downfall of global terrestrial biodiversity by 2050 and redress it to a pre-1970 level by 2100. Although robust, sophisticated and well-illustrated, the conclusions of this paper cannot alone be used to frame a post-2020 biodiversity strategy.